Congenital diaphragmatic hernia; masquarding as hydropneumothorax - Yadav, RP; Agrawal, CS; Pathania, OP; Shrestha, P; Sharmal, S; Shrivastaw, M (Journal of College of Medical Sciences-Nepal, 2014)
Congenital diaphragmatic hernia occurs in about 1 in 3000 births among which over 90% of the patients will be diagnosed either antenatally or will present with respiratory distress in the first few hours of life and about 5% to 30% of diaphragmatic hernias present beyond the neonatal period. The extent of herniation of abdominal viscera into the thorax may vary, leading to acute or intermittent symptoms. The inappropriate insertion of a chest drain, although relieving the symptoms temporarily, may result in serious consequences by damaging intrathoracic abdominal viscera. Journal of College of Medical Sciences-Nepal, 2013, Vol-9, No-3, 54-56 DOI: http://dx.doi.org/10.3126/jcmsn.v9i3.10223